PRAKTIK TEATER POSTDRAMATIK DI INDONESIA - H, Afrizal; N, Sahrul; Yusril, Yusril (Paradigma: Jurnal Kajian Budaya, 2023)
The article entitled "Practice of Postdramatic Theater in Indonesia", is an examination of the practice of postdramatic theater in Indonesia in the 1990s to 2000s in Jakarta, Bandung, Yogyakarta, and even West Sumatra. This practice spawned generations that continue to grow and develop through aesthetics based on performance texts, outside of the conventional drama texts that we understand so far. Each theater community, regardless of whether it is postdramatic or not, has carried out an in-depth exploration and elaboration of all possible bodies, texts and artistic materials which are used as the main capital of performances. This study uses qualitative methods, with several theories, namely; historical theory and postdramatic theater theory. The process of composing, structure, and texture of postdramatic theater developed by Hans-Thies Lehmann is centered on the elements of text, space, time, body, and media depicted in the works of SAE Theatre, Grave Theater, Black-and-White Payung Theatre, Garage Theatre, and Black-White Art Community.